PEKALONGAN MSMEs PREPARE PRODUCTS TO PENETRATE THE HALAL MARKET AND ECOSYSTEM - Mardhiyah, Dien; Widiastuti, Tika; Mawardi, Imron; Hartini, Sri; Rosidi, Dinda Oktaviona; Zain, Nur Habiba; Apriwiliza, Gita (Universitas Airlangga, 2024)
The low marketing literacy of MSMEs in Kaliombo Village, Pekalongan Regency, has resulted in low marketing activities such as packaging, product branding, and digital marketing. Apart from that, the literacy of MSME actors in the Village regarding halal products is still low, so they require readiness for the marketed products to comply with Government Regulations regarding Halal Product Guarantees. This government regulation requires that all products traded are halal so that they enter the halal ecosystem. This community service is carried out with training and mentoring activities to increase literacy regarding the importance of branding, packaging, digital marketing, and halal-haram to prepare MSME residents of Kaliombo Village to face competition in the market and enter the halal ecosystem. This empowerment includes socialization and assistance regarding concepts, uses, and how to apply branding, packaging, digital marketing, and halal-haram to the Kaliombo Village community farmer groups. This empowerment has an impact on increasing the competitiveness of MSMEs through optimizing brand design, packaging design, creating and developing social media accounts, and preparing to self-declare for halal certification permits for MSMEs.